ANALISIS PERFORMA WEBSITE MIND & SOUL MENGGUNAKAN GTMETRIX DAN WEBPAGETEST - Ham, Ficky; Musdar, Izmy Alwiah; Hasniati (STMIK KHARISMA Makassar, 2024)
The Mind & Soul website is a website-based application developed to facilitate users in ordering and processing mental health counseling online with a counselor which can be accessed via the link https://mindandsoulofficial.com/. The performance of the Mind & Soul website requires detailed analysis to find out what the website's performance is like and what deficiencies the Mind & Soul website has. The purpose of this research is to test the performance of the Mind & Soul website using GTMetrix and WebPageTest so as to find out the performance details. Performance testing on the Mind & Soul website will be carried out using two tools, namely GTMetrix and WebPageTest. The collection method was carried out using the observation method, in which the researcher tested directly on the Mind & Soul website using GTMetrix and WebPageTest tools. Based on the results of the Mind & Soul website performance test on GTMetrix, all desktop and mobile website pages got grade A which means very good, while the results of the performance test using WebPageTest showed that the speed of all desktop and mobile pages is not bad and some pages still need to be improved from usability and ductility factors.